Fatigue and illness in athletes - Nimmo, M. A.; Ekblom, B. (Journal of Sports Sciences, 2007)
Adequate nutrition before, during, and after training and competition is a key element to maintaining health. During both sprint and endurance exercise, the availability of glycogen is fundamental to performance and any deficit will lead to early fatigue. In addition, strategies to offset the negative effects of the products of metabolism are presented. Although nutritional strategies can attenuate the immunosuppressive effects of exercise, there remains a period of susceptibility to infection after a hard exercise session and when this is repeated without sufficient recovery an athlete can enter a period of "overtraining" during which performance deteriorates. The aetiology and identification of this state is not clear and some current ideas are discussed. Finally, gastrointestinal problems during running can negate any training benefits and we propose some suggestions to reduce this problem.